1984
DOI: 10.1210/endo-115-3-1102
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptors on Pancreatic Acinar Cells in Guinea Pigs*

Abstract: The characteristics of interaction of insulin with specific receptors on exocrine pancreatic cells of the guinea pig have been studied. Insulins from different species as well as certain insulin analogs were found to have affinities to receptors on pancreatic acinar cells which are similar to what have been described for insulin receptors in other organs of different mammalian species. Binding was rapid and reversible at 37 C but dissociation was markedly slower at 12 C. Clear indications of negative cooperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Insulin is believed to bind to its own receptor on the acinar cell (128,168,183,211), leading to stimulation and potentiation of amylase secretion by various mechanisms including regulation of amylase gene transcription (90); stimulation of DNA, RNA, and acinar protein synthesis (89,129,145); and increase in glucose uptake (209).…”
Section: Pancreatic Hormones and Neuropeptidesmentioning
confidence: 99%
“…Insulin is believed to bind to its own receptor on the acinar cell (128,168,183,211), leading to stimulation and potentiation of amylase secretion by various mechanisms including regulation of amylase gene transcription (90); stimulation of DNA, RNA, and acinar protein synthesis (89,129,145); and increase in glucose uptake (209).…”
Section: Pancreatic Hormones and Neuropeptidesmentioning
confidence: 99%
“…It has been reported that insulin receptor exists in the membrane of the pancreatic acinar cells [4-6], and insulin directly enters to the acinar cells [7]. These findings suggest that insulin directly acts acinar cells and has important role to maintain exocrine secretion in the acinar cells.…”
mentioning
confidence: 96%
“…
The pancreatic acini are in close contact with the surrounding islets, having no significant fibrous capsules, and receptors of insulin [1][2][3][4] and somatostatin [5,6] on the pancreatic acinar cell have been reported. Therefore, this might eventually enter into very close interrelation between the exocrine pancreas and the endocrine islet of Langerhans.

The secretion of the pancreatic acinar cells has for a long time been thought to be regulated by the islet hormones [7], but few detailed studies indicate hormonal regulation of the acinar cells.

…”
mentioning
confidence: 99%